2019
DOI: 10.1159/000495947
|View full text |Cite
|
Sign up to set email alerts
|

Distinguishing Lipedematous Scalp, Lipedematous Alopecia, and Diffuse Alopecia Areata

Abstract: Soft, spongy or doughy consistency of the scalp resulting from thickening of the subcutaneous layer is termed as lipedematous scalp (LS). When such soft, boggy scalp is associated with hair loss, where the scalp hair is no longer than a few centimeters, it is referred as lipedematous alopecia (LA). There have been coincidental reports of androgenetic alopecia, psoriasis, mucinosis, and discoid lupus erythematosus with LS. We report a case of LS and alopecia areata whose characteristic histopathological feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…Lipedematous alopecia refers to the condition where hair growth abnormalities co-exist with lipedematous scalp. Lipedematous alopecia may be confused with other causes of localised hair loss such as alopecia areata [1]. Herein, we report a case of lipedematous scalp and alopecia present at the same site over the scalp.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Lipedematous alopecia refers to the condition where hair growth abnormalities co-exist with lipedematous scalp. Lipedematous alopecia may be confused with other causes of localised hair loss such as alopecia areata [1]. Herein, we report a case of lipedematous scalp and alopecia present at the same site over the scalp.…”
Section: Introductionmentioning
confidence: 89%
“…Sahu et al reported concomitant alopecia areata and lipedematous scalp over parietotemporal region of scalp in a 29 year old male [7]. Dhurat et al also described a similar case and emphasized that lipedematous scalp and lipedematous alopecia are not distinct conditions [1].…”
Section: Case Reportmentioning
confidence: 96%
“…7 Especially since the majority of social media users are young adults, the question arises whether this group is a growing user of aesthetic treatments such as botox and fillers. 8 According to a 2018 survey by the American Academy of Facial Plastic and Reconstructive Surgery, 72% of facial plastic surgeons saw an increase in cosmetic surgery or injectables in patients under the age of 30. This would be an increase of 24%, compared to 2013.…”
Section: Increased Usage Of Botulinum Toxin and Hyaluronic Acid Fillementioning
confidence: 99%
“…The unique finding of a more superficial blood flow with obliteration of the dermal-epidermal junction may help to understand the pathogenesis of these conditions. Deep scalp biopsies and imaging techniques may be helpful to rule out mainly alopecia areata, androgenetic alopecia 8 and other scalp conditions that course with pruritus and erythema such as psoriasis, scalp dermatitis and dermatomyositis. LS and LA may be an expression of the same scalp disorder, with an unclear pathogenesis background and distinctive clinical features.…”
mentioning
confidence: 99%
See 1 more Smart Citation